Importance of mammary system conformation traits in selection of Jaffarabadi buffaloes for milk production (Indian Journal of Animal Production and Management, 2024)
A study was carried out to know the relationship between variation in mammary system conformation traits  and milk yield in Jaffarabadi buffaloes. 150 buffaloes selected from dairy farms located in and around  Hyderabad were utilized for the study. Among udder shapes, bowl shaped udder was most common followed  by globular, pendulous and goaty udder with 53.3%, 26.66%, 16% and 4%, respectively and cylindrical  shaped teats was most common followed by conical, funnel, pear and bottle shapes with 48.0%, 22.66%,  13.33%, 10% and 6%, respectively. The average udder length, width and depth in buffaloes ranged from  62.64 ± 0.74 (globular udder) to 67.81 ± 1.03 cm (pendulous udder), 50.51 ± 0.35 (bowl udder) to 54.07 ±  1.35 cm (goaty udder) and 17.26 ± 0.27 cm (bowl udder) to 20.25 ± 0.74 cm (goaty udder), respectively.  Positive and highly significant (P
Keywords: Jaffarabadi buffalo; Milk Yield; Teat biometrics; Teat shape; Udder biometrics; Udder shape